The Impact of an Intergenerational Dance Project on Older Adults’ Social and Emotional Well-Being - Douse, Louise; Farrer, Rachel; Aujla, Imogen (Frontiers in Psychology, 2020)
There has been strong interest in intergenerational arts practice in the UK since the 1980s, however, there is a generally weak evidence base for the effectiveness of intergenerational practice regardless of the domain. The aim of this study was to investigate the outcomes of an intergenerational arts project on participants’ social and psychological well-being using a mixed methods, short-term longitudinal design. Generations Dancing brought together community artists with students (N=25) and older adults (N=11) living in Bedford. Over an 11 week period, participants worked together to produce a new dance performance and photography exhibition. Focus groups were conducted with the participants to explore their feelings about the collaboration across generations and communities. Participants also completed a battery of questionnaires pre- and post-project, to assess any change in their levels of well-being. Results indicate that the older adults showed increased confidence and willingness to connect with others; they got immense enjoyment from talking about their experience with others. Furthermore, the project helped to address negative stereotypes that the older adults had of working with the young people. The older adults enjoyed the students’ company and felt encouraged and supported by the young people. While a small number of challenges were identified, including difficulties in travelling to the workshops for vulnerable participants, most challenges were over-come through the older adults’ engagement in the project. For example, initial anxieties regarding the performance seemed insufficient to affect the participants’ overall enjoyment of the project. The findings were supported by the increased scores in relatedness, affect and social well-being over time, though were not statistically significant. The results of this study indicate that intergenerational dance and arts projects can have wide-reaching positive impacts on both social and psychological well-being. However, there were a number of methodological challenges, including difficulty in recruiting sufficient numbers of both experimental and control groups for a robust quantitative evaluation of the data. These challenges highlight that ‘real life’ settings and scenarios can influence the amount, nature, validity and reliability of data collected. Going forward we encourage researchers to continue to consider innovative ways to address such methodological challenges.